Additional taxonomic coverage of the doubly uniparental inheritance in bivalves: Evidence of sex‐linked heteroplasmy in the razor clam Solen marginatus Pulteney, 1799, but not in the lagoon cockle Cerastoderma glaucum (Bruguière, 1789). (13th May 2020) - Lucentini, Livia; Plazzi, Federico; Sfriso, Andrea Augusto; Pizzirani, Claudia; Sfriso, Adriano; Chiesa, Stefania
Abstract: In animals, doubly uniparental inheritance (DUI) is a major exception to the common strict maternal inheritance of mitochondria. To date, DUI has only been found in many bivalve species, but its distribution is still unclear. Given the great species richness of the class, much effort is needed to further investigate the occurrence of DUI in unsampled species. A compelling evidence of DUI is generally the presence of a sex‐linked heteroplasmy, where two divergent mitochondrial lineages are found: One is isolated from the male germline, and the other one is isolated from the female germline and, normally, from the soma of both sexes. In the present study, we investigated the sex‐linked heteroplasmy in the razor clam Solen marginatus Pulteney, 1799 and in the lagoon cockle Cerastoderma glaucum (Bruguière, 1789) using two mitochondrial markers ( cox1 and rrnL ). We found evidence of DUI in the species S. marginatus, with a divergence up to 21% for the rrnL gene, but not in C. glaucum . Moreover, our phylogenetic reconstruction includes all the available data for heterodont species with sex‐linked heteroplasmy and suggests multiple origins of DUI in this subclass, as well as the presence of DUI in other species of the genus Solen . Abstract : Sex‐linked heteroplasmy has been investigated in Solen marginatus and Cerastoderma glaucum using two mitochondrial markers ( cox1 and rrnL ). Sex‐linked heteroplasmy has been detected in S. marginatus but not in C. glaucum. Evidence of DUI has been found in the species S. marginatus, but not in C. glaucum . Data also suggest multiple origins of DUI in heterodont subclass, as well as the presence of DUI in other species of the genus Solen .